Art of not being governed: an anarchist history of upland Southeast Asia - Scott, James C. (New Delhi, 2010)
For two thousand years the disparate groups that now reside in Zomia (a mountainous region the size of Europe that consists of portions of seven Asian countries) have field the projects of the organised state societies that surround them slavery, conscription, taxes, corvee labour, epidemics and warfare. Significantly, writes James C.Scott in this iconoclastic study, these people are not innocent who have yet to benefit from all that civilization has to offer; they have assessed state-based civilizations and have made a conscious choice to avoid them. The book is essentially an anarchist history , the first-ever examination of the huge literature on state-making that evaluates why people would deliberately and reactively remain stateless. Among the strategies employed by the people of Zomia to remain stateless are physical dispersion in rugged terrain; agriculture practices that enhance mobiliy; pliable ethnic identities; devotion to prophetic, millenarian leaders; and maintenance of a largely oral culture that allows them to reinvent their histories and genealogies as they move between and around states. The Art of Not Being Governed challenges us with a radically different approach to history that views events from the perspective of stateless peoples and redefines state-making as a form of internal colonialism. In contrast to the Western ideal of the social contract as fundamental to state-making Scott finds the disturbing mechanism of subjugation to be more in line with the historical facts in mainland area studies that will be applicable to other runaway, fugitive, and marooned communities, they Gypsies, Cossacks, tribes fleeing slave raiders, Marsh Arabs, or San-bushmen. In accessible language, James Scott, recognized worldwide as an eminent authority in Southeast Asian, peasant, and agrarian studies, tells the story of the peoples of Zomia and their unlikely odyssey in search of self-determination. Along the way he redefines our views on Asian politics, history, and demographics, and even our fundamental ideas about what constitutes civilization.
Keywords: Ethonology